Sex Offenders’ Perceptions of the Police and Courts: Are There Spill-Over Effects? - Brown, Sarah J. (Criminal justice and behavior, 2018)
Individuals convicted of sexual offenses are rarely asked their views of the police and courts. The aims of this study were to examine the impact of feelings of guilt on perceptions of the police and police interview outcomes and spill-over effects from perceptions of the police to perceptions of the courts. Participants were 116 adult males incarcerated for sexual offenses who were invited to report their perceptions of police interviewers, feelings at the time of interview, interview outcomes, and perceptions of the court process. Feelings of guilt were related to perceptions of the police. Both feelings of guilt and perceptions of the police were associated with interview outcomes. Spill-over effects were found as perceptions of the police were directly related to perceptions of the courts. The findings highlight the important role of police officers as gatekeepers to the criminal justice system, with associated implications for police officers’ training and practice.